Incidence of sudden cardiac death in Germany: results from an emergency medical service registry in Lower Saxony - Martens, Eimo (Europace, 2014)
AIMS: Sudden cardiac death (SCD) is among the most common causes of death in western countries including Germany. Whereas risk stratification and primary prevention is still insufficient, we also lack accurate incidence estimates. Current estimates vary widely (18.6–128/100 000/year), but data on SCD incidence in Germany are missing. Depending on SCD definitions, death needs to occur between 1 and 24 h after the onset of symptoms. METHODS AND RESULTS: In the district of Aurich (190 000 inhabitants, Lower Saxony, Germany), emergency medical service (EMS) is provided by a district government operated single carrier and two hospitals. To evaluate all EMS calls in this district from 2002 to 2009, we obtained EMS protocols, medical records, and death certificates for data analysis and adjudication of SCD. We defined SCD according to the definition of the World Health Organization, considering patients with cardiac arrest within ≤1 h after the onset of symptoms. We also required cardiopulmonary resuscitation being performed by EMS personnel. The overall mortality rate in the district of Aurich (1060/100 000/year) corresponded well with the average mortality rate in Germany (1030/100 000/year). During the observation period, we adjudicated 1212 SCD cases, equivalent to an annual rate of 151 SCD cases (81 cases/100 000/year). Rates remained remarkably stable over time, and affected a considerable number of individuals of working age (32/100 000/year). CONCLUSION: Consistent with prior reports, the SCD incidence in a district of Germany is substantial. Despite an elaborate EMS system and advanced medical care, SCD rates remain stable and necessitate improved, individualized risk stratification.